High-dimensional coherent one-way quantum key distribution - Kfir Sulimany; Guy Pelc; Rom Dudkiewicz; Simcha Korenblit; Hagai S. Eisenberg; Yaron Bromberg; Michael Ben-Or (npj Quantum Information)
Abstract High-dimensional quantum key distribution (QKD) offers secure communication with key rates that surpass those of QKD protocols utilizing two-dimensional encoding. However, existing high-dimensional QKD protocols require additional experimental resources, such as multiport interferometers and multiple detectors, thereby increasing the cost of high-dimensional systems and limiting their use. We introduce and analyze a high-dimensional QKD protocol that requires only standard two-dimensional hardware. We provide security analysis against individual and coherent attacks, establishing upper and lower bounds on the secure key rates. We tested our protocol on a standard two-dimensional QKD system over a 40 km fiber link, achieving a twofold increase in secure key rate compared to the standard two-dimensional coherent one-way protocol, without any hardware modifications. This work offers a significant improvement in the performance of already deployed QKD systems through simple software updates and holds broad applicability across various QKD schemes, making high-dimensional QKD practical for widespread use.